Development of Organic Rice Cultivation through Dual System of Azolla microphylla in Gentungan, Mojogedang, Karanganyar, Indonesia - Dwi Priyo Ariyanto; Aktavia Herawati; Jauhari Syamsiyah; Komariah Komariah; Ganjar Herdiansyah (PRIMA: Journal of Community Empowering and Services, 2023)
The use of Azolla microphylla (Azolla) as organic fertilizer or green manure is not yet known by the Farmer Group (FG) of Tani Mulyo 1 and Tani Mulyo 5. Moreover, dual system of Azolla is applied to organic rice cultivation. The dual system of Azolla uses Azolla as a fertilizer and as a deterrent to the growth of weeds that interfere with rice plants. This partnership program aims to increase partners' knowledge about the dual system of Azolla and assistance and direct practice of Azolla application on cultivated organic paddy fields. The stages include socialization, counseling, mentoring, practice of Azolla application, and monitoring-evaluation. The results showed that the participants' knowledge about Azolla before the activity was 25% very not know, 45% not know, and 15% know enough. There was an increase in participants' understanding after the activity, 65% know and 25% very know or increased up to 100% compared to before the activity. The results of participant satisfaction showed that 65% of participants were satisfied and 10% are very satisfied with the activities carried out. As many as 70% of the partners stated that they would apply the dual system of Azolla in organic rice cultivation. The increasing understanding and awareness of partners will affect the development of organic rice cultivation.